The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1089/omi.2017.0019
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association and Replication Study of Hepatotoxicity Induced by Antiretrovirals Alone or with Concomitant Anti-Tuberculosis Drugs

Abstract: Drug-induced hepatotoxicity (DIH) is a common adverse event that is associated with both antiretroviral (ARV) and anti-tuberculosis drugs (ATD). Moreover, the genetic variations predisposing ARV-and ARV-ATDinduced liver toxicity in African populations are not well investigated, despite the two diseases being the major global health problems in sub-Saharan Africa. We performed a genome-wide association study (GWAS) and replication study to identify the genetic variants linked to the risk of developing DIH due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…Similar to the findings in two earlier GWAS involving Europeans, 20,21 we failed to detect genomewide significance when we undertook a GWAS in the Indian population. This is in contrast to the recent GWAS performed on a Thai population, where genomewide significance was seen for NAT2 , 19 but is more consistent with a separate GWAS performed in Ethiopians, which also failed to observe genomewide significant signals, 38 although the Ethiopian patients were also undergoing HIV treatments that can cause DILI. In our enlarged European population, which includes the previously studied cases 20,21 as well as eight new cases, 29 we did see one genomewide significant signal in an intronic SNP in ASTN2 .…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Similar to the findings in two earlier GWAS involving Europeans, 20,21 we failed to detect genomewide significance when we undertook a GWAS in the Indian population. This is in contrast to the recent GWAS performed on a Thai population, where genomewide significance was seen for NAT2 , 19 but is more consistent with a separate GWAS performed in Ethiopians, which also failed to observe genomewide significant signals, 38 although the Ethiopian patients were also undergoing HIV treatments that can cause DILI. In our enlarged European population, which includes the previously studied cases 20,21 as well as eight new cases, 29 we did see one genomewide significant signal in an intronic SNP in ASTN2 .…”
Section: Discussionsupporting
confidence: 72%
“…to observe genomewide significant signals, 38 although the Ethiopian patients were also undergoing HIV treatments that can cause DILI. In our enlarged European population, which includes the previously studied cases 20,21 as well as eight new cases, 29 we did see one genomewide significant signal in an intronic SNP in ASTN2.…”
Section: Discussionmentioning
confidence: 99%
“…The slow metabolites of UGT1A6 and UGT1A9 are related to the liver injury induced by tolcapone ( Alfirevic and Pirmohamed, 2012 ), which may be due to the decrease of enzyme activity and the accumulation of toxic substances. In addition, the UGT2B7 rs7439366 allele is associated with an increased risk of diclofenac-induced liver damage ( Daly et al, 2007 ; Petros et al, 2017 ), and the mechanism may be the allelic variation leading to the formation of active diclofenac metabolites that trigger DILI.…”
Section: Dili and Gene Polymorphismmentioning
confidence: 99%
“…Chinese patients with the nuclear export protein 1 ( XPO1 ) rs4430924 AA genotype were also at significantly higher risk of developing antituberculosis drug-induced hepatotoxicity than those with the GG genotype ( He et al, 2019 ). In antiretroviral therapy, rs199650082 of nucleus signaling-1 ( ERN1 ) is significantly related to DILI, while in antiretroviral therapy combined with anti-tuberculosis therapy, transcriptional variation of synaptotagmin 1 ( Syt1 ) rs4842407 is associated with DILI ( Petros et al, 2017 ). Syt1 is a long intergene non-coding RNAs (lincRNAs) on chromosome 12, which plays a vital role in endocytosis, exocytosis, and the perception of Ca2+ concentration during vesicle transport; a recent experiment has shown that inhibiting its expression can inhibit the invasion and metastasis of liver cancer ( Xu et al, 2020 ).…”
Section: Dili and Gene Polymorphismmentioning
confidence: 99%
“…Three downstream genes associated with rs2331413 are likewise endoplasmic reticulum proteins. The ERN1 locus has been associated with several phenotypes in GWAS studies, most notably drug induced hepatotoxicity (Petros et al (2017)).…”
Section: Novel Biological Findingsmentioning
confidence: 99%